Genetic progress in coffee progenies by different selection criteria - Rezende, Juliana Costa de; Botelho, Cesar Elias; Oliveira, Antonio Carlos Baião de; Silva, Felipe Lopes da; Carvalho, Gladyston Rodrigues; Pereira, Antonio Alves (Coffee Science - ISSN 1984-3909, 2014)
In order to investigate the aspects related to the use of selection indexes in Coffea arabica breeding, analytical procedures were used: index based on the sum of ranks of Mulamba and Mock (ISR), index of desired gains of Pesek and Baker (DGI), classic index of Smith and Hazel (CI), base index of Williams (BI), and direct and indirect selection (DIS). Thirty-nine progenies were evaluated in the 4th generation by selfing after the 2nd backcross between “Catuai” and “Mundo Novo”. The evaluations were realized in coffee plants from 30 months old on, having the following characteristics: yield of eight harvests, classification for blend 16 and over, percentage of floating fruits, vegetative vigor and percentage of flat beans. The analytical procedures of selection indexes showed possibilities of applications in advanced generations of breeding being superior when compared with DIS. The DGI was not appropriate in the situation analyzed in this work. The selection based on CI and BI was the criteria that showed the best results in terms of gains in yield and grain size, and in the distribution of gains in the other characteristics.